Serological Patterns of Hepstitis B Virus Among HBsAg Negative Blood Donors in Baghdad, Iraq by Using Architect System - Hassab, Zainab S.; Abd Al-Ruhman, Amani K.; Saleh, Yakub A.; Abd Allah, Auroba I. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: About 10-15% of population HBV infection becomes chronic, and 85-90% are resolved. In Iraq, HBs-Ag assay by ELISA is only mandatory test for detection of HBV infection in blood donors. Anti- HBc and anti-HBs were not detectable in their sera. Objective: To investigate the distribution of serological patterns for HBV who were HBsAg negative. Material and method: Between July 18, 2011 to December 25, 2011, 10ml of blood samples were collected from National blood Transfusion Center donors, Baghdad, for 25782 individuals (25294 male, 488 female), mean age (20-65)years. HbsAg positive sera excluded (185), and final number of donors included in the study was 25597 HbsAg negative. Result: The data showed a previous exposure for HBV(p>0.05) through anti-HBc and anti-HBs 3.8% by Architect system. The anti-HBs combine with anti-HBc was 68.5%, while anti-HBc alone was 31.5%. Independent risk factors were association with married, history of blood transfusion and residence. Conclusion: The prevalence of the HBV in Iraq is 4.6% as intermediate region at first time.